The branch banker : today and tomorrow - Institute of Bankers (Great Britain) (London : The Institute, 1975)
This book provides a timely opportunity to consider where branch banking is heading and what the job of the branch manager will probably be like in the years that lie immediately ahead.
Based on the Seminar held at Christ's College, Cambridge, 6-12 September, 1975.
Proceedings of The Institute's sixth Cambridge Seminar.
Errata slip inserted.
Bibliography: p. 91-92.
usc 23/05/17
Loans
Keywords: Branch banks